Cinemas and Theatres: Elements of the Cultural Offer in the Management of Free Time - Szafrańska, Ewa; Napierała, Tomasz (Turyzm/Tourism, 2007)
The article consists of three parts. In the first the authors review definitions of free time and the ways it is organized. The second, devoted to the issue of cultural activity, is based on the literature and the published results of empirical studies from official Polish social statistics. The third is a discussion of a survey carried out among Lodz cinema and theatre-goers in February 2006.